A Systematic Review of Health Care Provider‐Perceived Barriers and Facilitators to Routine HIV Testing in Primary Care Settings in the Southeastern United States. (May 2018) - Tan, Kelly; Black, Beth Perry
Abstract : N/A: Despite efforts to improve HIV screening and testing, many primary care settings do not follow established guidelines. The purpose of our systematic review was to describe health care providers' perceived barriers and facilitators to testing for HIV at poorly used/novel testing sites in the southeastern United States. PubMed, CINAHL, and Embase databases were searched for peer‐reviewed studies of providers' perceived barriers and facilitators to routine HIV testing from January 2016 to April 2017 according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement. Of 708 papers retrieved, 12 met inclusion criteria and were analyzed. Barriers to HIV testing in primary care existed at the societal, organizational, and individual levels. Providers need continuing sexual health education, including HIV and federal guideline updates, and students should have clinical experiences to supplement knowledge about sexual health. Clinic protocols should be updated to meet current policy guidelines.